Predictors of Success Of Vaginal Birth After Previous Cesarean Section: An Analysis of 100 Cases - Qadir, Maimoona; Amir, Sohail (Journal of Gandhara Medical and Dental Science, 2017)
BACKGROUND Women eligible for vaginal birth after cesarean section (VBAC) have lower morbidity rates than women who undergo subsequent elective cesarean sections. Objective: To identify the obstetric parameters those influence the success of vaginal delivery in women with previous cesarean section. METHODOLOGY This descriptive cross sectional study was conducted at Gynaecology and Obstetrics Department of Khyber Teaching Hospital, Peshawar from 1st May 2015 to 31st April 2016.Inclusion criteria was all women of any age or parity presenting at >36weeks gestational age, with singleton pregnancy, vertex presentation, estimated fetal weight of 2.5 -3.5kg and documented previous lower uterine segment cesarean section for a non recurrent cause. Five predictors of success of vaginal birth after previous cesarean including maternal age, gestational age, and history of vaginal delivery, onset of labor and bishop score were evaluated in each patient. RESULTS Out of 100 women, 64 had VBAC and 36 had cesarean section. Fifty five were booked and 45 were non booked. Total women with history of VBAC were 24, out of these 16(66%) had VBAC and 8(33%) had repeat cesarean section. Ninety three had spontaneous onset of labor whereas 7 were induced,88 patients had Bishop score >5,out of these 61(69%) ended in VBAC and 27(30.6%) had cesarean section. The most common age group where VBAC occurred in majority was 25- 35 years. Thirty nine (61%) women had period of gestation between 38weeks to 39weeks+6days. Mean maternal age was 29.42 + 3.54 years CONCLUSION History of vaginal delivery, spontaneous sonset of labor and Bishop score >5 are the factors which are associated with more chances of vaginal delivery after cesarean section.